2017
DOI: 10.1038/srep45503
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic dye adsorption and release performance of natural zeolite

Abstract: Clinoptilolite type of zeolite (CZ) is a promising material for biomedicine and pharmaceutics due to its non-toxicity, thermal stability, expanded surface area, and exceptional ability to adsorb various atoms and organic molecules into micropores. Using multiphoton microscopy, we demonstrated that individual CZ particles produce two-photon excited luminescence and second harmonic generation signal at femtosecond laser excitation, and adsorb photo-dynamically active dyes such as hypericin and methylene blue. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…A completely different pattern was observed when a droplet of nonadsorbing fluorescein was added to the slide. 16 In this case, TPEL of fluorescein molecules has roughly uniform distribution, and CZ particles do not accumulate anionic fluorescein molecules in contrast to cationic MB, and SHG radiation from CZ particles is not quenched by fluorescein molecules. 16 Similar multiphoton imaging showed that CZ effectively adsorbed photodynamically active HYP from aqueous solutions.…”
Section: Adsorption Properties Of Cz Particlesmentioning
confidence: 89%
See 4 more Smart Citations
“…A completely different pattern was observed when a droplet of nonadsorbing fluorescein was added to the slide. 16 In this case, TPEL of fluorescein molecules has roughly uniform distribution, and CZ particles do not accumulate anionic fluorescein molecules in contrast to cationic MB, and SHG radiation from CZ particles is not quenched by fluorescein molecules. 16 Similar multiphoton imaging showed that CZ effectively adsorbed photodynamically active HYP from aqueous solutions.…”
Section: Adsorption Properties Of Cz Particlesmentioning
confidence: 89%
“…16 In this case, TPEL of fluorescein molecules has roughly uniform distribution, and CZ particles do not accumulate anionic fluorescein molecules in contrast to cationic MB, and SHG radiation from CZ particles is not quenched by fluorescein molecules. 16 Similar multiphoton imaging showed that CZ effectively adsorbed photodynamically active HYP from aqueous solutions. Taking into account the sizes of the used dyes, one can make preliminary conclusion that the mesoporosity, negative charge of CZ, and hydrophobicity of dyes play main role in adsorption processes in CZ-dye systems.…”
Section: Adsorption Properties Of Cz Particlesmentioning
confidence: 89%
See 3 more Smart Citations